« ¡Democracia real antes ! » : Genèse de mobilisations citoyennes pour la démocratie participative dans l’Espagne pré-15M - Mathias Rull Jan (Cahiers de Civilisation Espagnole Contemporaine)
The article looks at some social initiatives that promoted participatory democracy in Spain during the first decade of the 21st century. These were rare, but constituted in some way precursors of the movement of Indignados, one of the central demands of which was the increase of citizen participation. After presenting these initiatives (location, years, precise demands, degree of achievement), we focus on the nature of the groups which carried them out. We see that, behind newly created collectives, are organizations that have been operating for a long time in the territory. And we wonder about the reasons which led these traditional actors of the place to formulate innovative demands. We will then see that the deepening of local democracy was not their only motivation. Finally, the text mentions elements which may have contributed not only to the emergence of these mobilizations, but also to their establishment over time.